PERSISTENT STAPEDIAL ARTERY SEBAGAI ANOMALI VASKULAR TELINGA TENGAH: SEBUAH TINJAUAN LITERATUR - Irwan Triansyah; Nadia Purnama Dewi; Melya Susanti; Ade Teti Vani; Dessy Abdullah (Yayasan Nusantara Hasana Berdikari, 2025)
Persistent Stapedial Artery (PSA) is a rare vascular anomaly of the middle ear that results from the failure of the stapedial artery to regress during embryonic development. Despite often being asymptomatic, PSA has significant clinical implications, particularly in middle ear surgery, where it increases the risk of intraoperative bleeding and nerve injury. This review was conducted through a systematic search of PubMed, Scopus, and Google Scholar using the keywords “persistent stapedial artery,” “middle ear,” and “vascular anomaly.” Included articles comprised case reports, case series, and literature reviews from the past 10 years addressing embryology, clinical manifestations, diagnosis, and management of PSA. The findings indicate that PSA can be identified across different age groups, most often incidentally through temporal bone imaging or otologic procedures. In symptomatic cases, clinical features may include pulsatile tinnitus and conductive hearing loss. Temporal bone CT typically demonstrates the absence of the foramen spinosum and the presence of abnormal vascular channels in the tympanic cavity. Management varies, ranging from observation in asymptomatic cases to surgical intervention in patients with symptoms or complications. Although rare, recognition of PSA is critical to prevent intraoperative complications. Further studies are required to clarify the prevalence and define optimal therapeutic strategies. Meanwhile, heightened awareness among otolaryngologists and radiologists can improve diagnostic accuracy and patient safety.